Tatalaksana Pemeliharaan Ternak Ruminansia dengan Baik - Noywuli, Nicolaus; Ngaku, Maria Alfonsa; Beo, Maria Ortin; Bunga, Maria Kristina; Meo, Rosadalima; Keu, Anselmus Soa (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
Animal husbandry is a group or individual activity that raising or breeding certain types of livestock such as cattle, goats and buffalo. Cattle, goats and buffaloes. Good animal husbandry management is a series of practices and procedures designed to improve animal welfare, efficiency and procedures designed to improve animal welfare, production efficiency and environmental sustainability. Production efficiency, and environmental sustainability. This research aims to identify and formulate guidelines for good animal husbandry management, which includes aspects of ruminants, goats and buffaloes. Guidelines, which include aspects of ruminant livestock, husbandry management, ruminant husbandry management, ruminant housing management, ruminant feed management, and livestock health management. The method in this article uses a library study (library research), which is a method of collecting data by understanding and studying theories from various literatures related to the research. with the research. Good management of ruminant livestock is of course what needs to be considered is housing, feed and health. of course, what needs to be considered is housing, feed and health. Development the construction of cages for ruminants needs to pay attention to the condition of the location to be built and away from residential areas. to be built and away from residential areas. Just like the establishment of cages far from settlements is to avoid residents' annoyance with the odour caused by ruminants. to avoid residents being disturbed by the odour caused by goats. from goats. Feed for ruminants is a source of nutrients needed to fulfil the needs of each animal. required to fulfil the life needs of each livestock where the food ingredients are favoured and can be digested well. conclusion of this study shows that the aspect of livestock maintenance in the conclusion of this study shows that aspects of livestock maintenance in achieving the conclusion of this study shows that the aspect of livestock maintenance in achieving optimal production, knowledge of livestock cultivation is absolutely knowledge of livestock cultivation is absolutely necessary for prospective farmers and livestock agencies.